THE EFFECTIVENESS OF USING AUTHENTIC MATERIALS IN IMPROVING ENGLISH AS A FOREIGN LANGUAGE (EFL)STUDENTS' READING COMPREHENSION(A QUASI EXPERIMENTAL STUDY OF THE FIRST GRADE STUDENTS OF SMAN 10 BANDUNG) - Laxmi Mustika Cakrawati, - (2009)
The study was aimed to investigate the effectiveness of using authentic materials in improving English as a Foreign Language (EFL) students' reading comprehension and to find out students' response towards the use of authentic materials in the classroom. The study applied quasi-experimental method by using non-equivalent control group pre-test and post-test design. The study was conducted in SMAN 10 Bandung and involved two classes of the first grade which were chosen based on purposive sampling. One class was taken as experimental group and another class was taken as control group. The data for this study were obtained through pre-test, post-test, and questionnaire and were analyzed by using SPSS 15.0 for Windows. The result of data analysis by using independent sample t-test shows that there is a significant difference in terms of mean between the students' post-test score in the experimental group (M = 78.05, SD = 9.307, SE = 1.490) and the students' post-test score in the control group (M = 66.77, SD = 13.460, SE = 2.155). It is supported by the result of t obtain (76) = 4.305 which is higher than t critical (2.000) with p (0.000) < 0.05 and also represented by a large effect size (r = 0.443). Moreover, based on students' responses on questionnaire, it is shown that students give positive response towards the use of authentic materials. Therefore, the findings of the study indicate that the use of authentic materials is effective in improving students' reading comprehension. This study is expected to give some benefits and valuable contribution to the process and development of teaching and learning English, especially reading.